2022
DOI: 10.1038/s41598-022-19467-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of return to work after various coronary events: meta-analysis of prospective studies

Abstract: Return to work (RTW) after a coronary event remains a major concern. This systematic review and meta-analysis of prospective studies published between January 1988 and August 2020, aim to evaluate the prevalence of RTW after a coronary event (myocardial infarction, acute coronary syndrome, angina pectoris) and to assess the determinants of RTW (such as follow-up duration, date of recruitment, country, gender, occupational factors, etc.). PRISMA and MOOSE guidelines were followed. Study quality was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…However, ACS may change patients’ perceptions of work stress, anxiety, depression, and job burnout throughout the follow-up period. Consequently, the latent risk of exposure misclassification due to changes of employment status and work-related stress cannot be excluded, as recent research evidence indicated that more than 80% employees would return to work after coronary events [ 62 ], and work stress might be increased afterwards [ 63 ]. For future research, it is important to conduct dynamic observations on these participants to understand the relationship between the change in patients’ work stress and CVD prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, ACS may change patients’ perceptions of work stress, anxiety, depression, and job burnout throughout the follow-up period. Consequently, the latent risk of exposure misclassification due to changes of employment status and work-related stress cannot be excluded, as recent research evidence indicated that more than 80% employees would return to work after coronary events [ 62 ], and work stress might be increased afterwards [ 63 ]. For future research, it is important to conduct dynamic observations on these participants to understand the relationship between the change in patients’ work stress and CVD prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Major progress in the diagnosis and in the treatment of acute coronary syndromes has been made in the last decades, and a decrease in mortality has been reported in several countries [ 1 ]. However, acute coronary syndromes still are a frequent pathology worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, teachers with acute coronary syndrome (ACS) may have reduced exercise tolerance to climb stairs in schools or conduct physical education classes. Based on a meta-analysis, nearly 20% of ACS survivors did not resume work ( Kai et al, 2022 ). Up to 75% of stroke survivors struggled in controlling their hand dexterity, making it difficult for teachers to write on the board or manipulate classroom materials.…”
Section: Introductionmentioning
confidence: 99%